2016
DOI: 10.21660/2016.24.160610
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Swelling Pressure Measured by the Oedemeter Method

Abstract: Expansive soils are common in arid and semi-arid climate regions of the world and cause severe problems on civil engineering structures. The Swelling potential of the expansive soil mainly depends upon the properties of soil and environmental factors, and stress conditions. Swelling pressure is a key parameter used in designing structures in and on expansive soil. The swelling pressure of soil is measured in the laboratory using a representative soil samples. The size and the surface friction of the sample rin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…Specifically, for moisture content of 10.10%, the swelling pressures were 29.92 kPa and 85.03 kPa while the dry densities were 0.14 kN/m 3 and 0.15 kN/m 3 , respectively. However, swelling pressure was 199.95 kPa for a dry density Jayalath et al [20], Çimen et al [24], and Dafalla [25] considered expansive stress decreased monotonically with a rise in the moisture content. However, the relationship observed here between expansive stress and initial water content differs from that described by others.…”
Section: Factors Influencing the Swelling Pressurementioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, for moisture content of 10.10%, the swelling pressures were 29.92 kPa and 85.03 kPa while the dry densities were 0.14 kN/m 3 and 0.15 kN/m 3 , respectively. However, swelling pressure was 199.95 kPa for a dry density Jayalath et al [20], Çimen et al [24], and Dafalla [25] considered expansive stress decreased monotonically with a rise in the moisture content. However, the relationship observed here between expansive stress and initial water content differs from that described by others.…”
Section: Factors Influencing the Swelling Pressurementioning
confidence: 99%
“…Meanwhile, there was no relation between expansive stress and moisture content if the vertical pressure was above a certain value. Jayalath et al [20] observed that the swelling pressure and dry density are positive correlation.…”
Section: Introductionmentioning
confidence: 98%
“…This area has been documented since the mid -1950's as a highly susceptible region for rainfallinduced slope failures [18][19][20][21]. Further, the region consists of expansive soil [22][23][24] which undergoes a significant volume change when drying and wetting. This soil needs to be stabilized before when lightweight structures such as roads, and residential houses are placed [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…34 Figure 2-19: (a) Variation of swelling pressure with dry density of several bentonites (Wang et al, 2012); (b) exponential correlation between swelling pressure and dry density of FEBEX bentonite materials (Hoffmann et al, 2007) …………………………………………………………………………………………………………………………. 35 Figure 2-20: Swelling pressure development in samples compacted at several dry densities and with distinct initial water contents (Jayalath et al, 2016) ………………………………………………………………………………. 35 Figure 2-21: Schematic representation of clay particle arrangements (after Lambe and Whitman, 1979) for undisturbed samples from (a) salt water and (b) fresh water deposits and for (c) remolded samples………………………………………………………………………………………………………………………………………………… 36…”
Section: List Of Figuresmentioning
confidence: 99%
“…Figure 2-22: (Swelling pressure development at different (a) cell diameters (for a sample height of 18.5 mm); (b) sample heights (for a cell diameter of 76.0 mm). Grease was applied on the inner surface of the cells (Jayalath et al, 2016)…………………………………………………………………………………………………………………….. 37 Figure 2-23: Swelling pressure development with (WG) and without (WOG) the application of grease on the inner surface of the oedometer cell (with a diameter of 76.0 mm and a height of 25.5 mm) (Jayalath et al, 2016)…………………………………………………………………………………………………………………………………………… 38 Figure 2-24: The effect of the remolding procedure on the swelling measured at distinct initial water contents for a clayey soil in Jordan (Attom et al, 2006)………………………………………………………………………… 39 Figure 2-25: (a) Microfabric of a clay predominantly constituted of clay aggregates with larger pores among them (Gens and Alonso, 1992); (b) microfabric of a soil composed mainly by elementary clay particles (Gens and Alonso, 1992); (c) micrograph of FEBEX bentonite compacted at dry density of 1.40 Mg/m 3 (Lloret and Villar, 2007); (d) micrograph of MX-80 compacted at dry density of 1.80 Mg/m 3 after wetting/drying cycles (Seiphoori et al, 2014)……………………………………………………………………………………….. 40 Figure 2-26: Pore size distribution of compacted samples made of a granular mixture of FEBEX bentonite pellets at several dry densities (Hoffmann et al, 2007)…………………………………………………………………………. 41 Figure 2-27(a) Effect of the compaction effort on the pore size distribution of compacted samples of FEBEX bentonite (Lloret et al, 2003); (b) development of the pore size distribution of compacted MX-80 bentonite/sand mixtures under wetting path (Wang et al, 2013) ………………………………………………………….…”
Section: List Of Figuresmentioning
confidence: 99%